P076 The effect of enalapril on preventing colon cancer in AOM/DSS-induced colitis-associated colon cancer model and xenograft model. (16th January 2018) - Han, Y M; Lee, C; Lee, J W; Kim, J H; Chun, J; Im, J P; Kim, J S
Abstract: Background: Enalapril, an angiotensin-converting enzyme (ACE) inhibitor, has pleiotropic effects such as anti-inflammatory effects. According to previous study, enalapril may block the NF- κ B signalling pathway, inhibit the activation of intestinal epithelial cells and macrophages, and attenuate experimental murine colitis by down-regulating IκBα phosphorylation. In this study, we evaluated the antitumour effect of enalapril in azoxymethane/dextran sodium sulfate (AOM/DSS)-induced colitis-associated colon cancer model and xenograft model. Methods: In AOM/DSS-induced colitis-associated colon cancer model, C57BL/6 mice (7-week-male) were given a single peritoneal injection of AOM (12 mg/kg) on day 0. Seven days later, 2% DSS was administered for 5 days and followed by free water consumption for 16 days. This cycle was repeated three times. Mice were divided into five group; negative control, vehicle, enalapril 1 mg/kg group, enalapril 5 mg/kg group, and 5-aminosalicylic acid (ASA) 75 mg/kg group. Enalapril and 5-ASA were dissolved in drinking water and the vehicle group received a comparable volume of drinking water from day 8. Body weight was measured every other day. The mice were euthanized 10 days after the last 2% DSS administration. After euthanization, colon length and tumour number were measured. In xenograft model, 2 × 10 6 HCT 116 cell was injected into right thigh of Balb/c nude mice (6-week male). Mice were divided into three group: vehicle, enalapril 1 mg/kg group, and enalapril 5 mg/kg group. Enalapril was administered in drinking water from 3 days before the HCT 116 cell injection till euthanization. The mice were euthanized on day 30. Body weight and tumour volume were measured every third day. Tumour volume was calculated using the formula: V (mm 3 ) = Π /6 × (smaller diameter) 2 × (larger diameter). Results: The administration of oral enalapril (5 mg/kg) significantly prevented weight loss and reduced tumour number in AOM/DSS-induced colitis-associated colon cancer model. The colon length was also significantly longer in enalapril (5 mg/kg) group. In xenograft model, the administration of oral enalapril inhibited tumour growth significantly. Conclusions: Our results indicate that oral supplementation with enalapril shows significant effect on colon cancer growth inhibition. These findings suggest that enalapril is a potential preventive agent for colon cancer.